Abordagem descritiva de topo de sistemas convectivos baseada em combinações de diferenças de temperatura de canais do METEOSAT-9 e modelo numérico - Silva Neto, Carlos Pinto da (2014)
Mesoescale Convective Systems (MCS) are the largest convective storms, and due to its capacity of destruction these storms are commonly associated with severe events. It is extremely important to have tools that help forecasting and monitoring phenomena of this magnitude. This study aimed to develop an approach for monitoring severe storms using images from Meteosat-9 and product of numerical weather prediction. More specifically, the method uses the infrared channel temperature, differences between the temperatures of the water vapor channel and infrared (WV-IR) and between IR channel and the tropopause temperature provided from the NCEP project / NCAR reanalysis. Was seeking to highlight regions of intense convective activity, the convective core of a storm, and rapid intensification. This methodology was put in test by applying it to 12 cases of MCSs occurred in southern South America in 2010. The cases were analyzed by the characteristics of brightness temperature, morphology of evolution and lifetime, as well as characteristics of the atmosphere observed by radiosonde, and compared to the results of the developed methodology. The approach was effective in highlighting areas of extreme convective activity. Negative values of the temperature difference IR-PNT (<-2 º) satisfactorily estimated the convective region, being possible to detach it from the stratiform region of a MCS. Storms that showed lower cloud top temperature, estimated by IR channel at its stage of maximum activity, showed high values of temperature difference WV-IR (> 3) in its initiation phase. For this feature was possible to estimate that such storms would be of great intensity since the first hours of existence. Individual analysis of the parameters of this methodology were not unanimous in classifying storms according to intensity. Was then created a function combining these parameters to classify the MCSs. This function applied to IR 10.8 channel images highlighted regions of intense convective activity masking clouds of low vertical development. The new approach developed can be extremely useful in operational centers and in research and comparison of convective systems.